Pengaruh RPM terhadap kapasitas hasil potongan Pemotong Batang Singkong (Petokong) Tipe TEP-1 - Asmara, Sandi; Amien, Elhamida Rezkia; Zulkarnain, Iskandar; Kuncoro, Sapto; Aditiya, Muhammad Kharisma (abe.fp.unila.ac.id, 2023)
The aim of this research were to analyze the RPM effect on the Petokong Type TEP 1 cutting capacity. The tools used include TEP-1 Type Cassava Stem Cutter, tachometer, stopwatch, 1000 ml measuring cylinder, 3.4 and 6 inch pulleys. The amount of bait used in this study was 2, 3, 4 cassava stalks. Revolutions per Minute (RPM) modification is done by using different pulley diameters. Pulleys with a diameter of 3 inches produce 3500 RPM, a diameter of 4 inches produces 2625 RPM, and a diameter of 6 inches produces 1750 RPM. Parameters observed in this study included working capacity, fuel consumption, and seed size uniformity. The best working capacity is owned by the B2R1 treatment combination of 9,900 seedlings/hour with the feed amount of 3 cassava stalks and 3500 RPM, while the lowest capacity is 6,000 seeds/hour produced in the B1R3 treatment with the feed amount of 2 cassava stems and 1750 RPM. Measuring fuel consumption is necessary using methods that are accurate and of long duration. In this study, the measurement of fuel consumption only lasted for 2 minutes using the method of adding fuel volume. This will cause a high error in the calculation. The use of Petokong produces a uniformity of above 95% which causes low seedling damage due to cutting.Keywords: Cassava Seeds, Cultivation of cassava, Lampung, Cutting machine, Pulley